Targeting MYCN upregulates L1CAM tumor antigen in MYCN-dysregulated neuroblastoma to increase CAR T cell efficacy - Laura Grunewald; Lena Andersch; Konstantin Helmsauer; Silke Schwiebert; Anika Klaus; Anton G. Henssen; Teresa Straka; Marco Lodrini; Sebastian G. Wicha; Steffen Fuchs; Falk Hertwig; Frank Westermann; et al. (Pharmacological Research)
Current treatment protocols have limited success against MYCN-amplified neuroblastoma. Adoptive T cell therapy presents an innovative strategy to improve cure rates. However, L1CAM-targeting CAR T cells achieved only limited response against refractory/relapsed neuroblastoma so far. We investigated how oncogenic MYCN levels influence tumor cell response to CAR T cells, as one possible factor limiting clinical success. A MYCN-inducible neuroblastoma cell model was created. L1CAM-CAR T cell effector function was assessed (activation markers, cytokine release, tumor cytotoxicity) after coculture with the model or MYCN-amplified neuroblastoma cell lines. RNA sequencing datasets characterizing the model were compared to publicly available RNA/proteomic datasets. MYCN-directed L1CAM regulation was explored using public ChIP-sequencing datasets. Synergism between CAR T cells and the indirect MYCN inhibitor, MLN8237, was assessed in vitro using the Bliss model and in vivo in an immunocompromised mouse model. Inducing high MYCN levels in the neuroblastoma cell model reduced L1CAM expression and, consequently, L1CAM-CAR T cell effector function in vitro. Primary neuroblastomas possessing high MYCN levels expressed lower levels of both the L1CAM transcript and L1CAM tumor antigen. MLN8237 treatment restored L1CAM tumor expression and L1CAM-CAR T cell effector function. Combining MLN8237 and L1CAM-CAR T cell treatment synergistically enhanced MYCN-overexpressing tumor cytotoxicity in vitro and in vivo concomitant with severe in vivo toxicity. We identify target antigen downregulation as source of resistance against L1CAM-CAR T cells in MYCN-driven neuroblastoma cells. These data suggest that L1CAM-CAR T cell therapy combined with pharmacological MYCN inhibition may benefit patients with MYCN-amplified neuroblastoma.